Stability of a Cylinder Resting on a Plane Rigid Surface-Regular Waves - Fan, Wei Kit (Universiti Teknologi Petronas, 2009)
Given the hostilc nature offshore environment, wave-induced instability is one of the major problems encountered in submarine pipeline analysis. The wave induced instability occurred due to the loading of the hydrodynamic forces cxciled by the propagating waves and currents on the submarine pipelines. The mama objective of this project is to determine the minimum in-line lorces leading to the point of instability of submarine pipelines subjected to exposure of regular waves. I or this project, the horiiontal stability of submarine pipelines under the exposure to regular waves as studied. I he project consisted of live stages namely literature and theory rcvic%%, fabrication of pipeline model, physical modeling, analyiation phase and the fittalüing of the I' inal Report.